2000
DOI: 10.1111/j.1469-7793.2000.t01-2-00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroeffector transmission to different layers of smooth muscle in the rat penile bulb

Abstract: Using intracellular recording techniques, two distinct layers of smooth muscle were identified in the rat penile bulb. The inner muscle layer (parenchyma) exhibited spontaneous action potentials, while the outer sheet (sac) was electrically quiescent. In the parenchyma, transmural stimulation initiated non‐adrenergic, non‐cholinergic (NANC) inhibitory junction potentials (IJPs) which were abolished by Nωnitro‐L‐arginine (LNA) or 1H‐[1,2,4]oxadiazolo[4,3‐a]quinoxalin‐1‐one (ODQ). The amplitude of IJPs was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…From our observations that ethanolic leaf extract of T. procumbens induces corporal relaxation responses in contractions produced by either of the agonists, it suggested that T. procumbens extract blocks Ca 2+ influx through interference with both voltage-and receptor-operated channels. Ca 2+ transients with the action potentials observed in this study were consistent with previous reports on corpus spongiosum smooth muscle [18,22]. This indicates that the activation of l-type Ca 2+ channels may be a fundamental process of spontaneous activity in CCSM.…”
Section: Discussionsupporting
confidence: 93%
“…From our observations that ethanolic leaf extract of T. procumbens induces corporal relaxation responses in contractions produced by either of the agonists, it suggested that T. procumbens extract blocks Ca 2+ influx through interference with both voltage-and receptor-operated channels. Ca 2+ transients with the action potentials observed in this study were consistent with previous reports on corpus spongiosum smooth muscle [18,22]. This indicates that the activation of l-type Ca 2+ channels may be a fundamental process of spontaneous activity in CCSM.…”
Section: Discussionsupporting
confidence: 93%
“…It does not exist in rabbit, while in man it is a slight enlargement of the proximal part of corpus spongiosum and in rat it is much more prominent (Hayes 1965). Canine (Hedlund et al 1995) and rat (Hashitani 2000) penile bulbs have been found to receive rich NANC innervation mediated by L‐arginine‐nitric oxide pathway similar to the corpus cavernosum . Consistently, in the present study we found that electrically‐induced relaxations of rat penile bulbs were abolished after incubation with tetrodotoxin and inhibited by the addition of L‐NAME indicating that they are neural in origin and are mediated by L‐arginine/nitric oxide pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of ion channels have been identified in CC smooth muscle cells, but there have been few electrophysiological investigations of whole corporal smooth muscle preparations ). In the proximal part of the rat corpus spongiosum (penile bulb), Hashitani (2000) demonstrated spontaneous action potentials in the inner muscle layer. On the other hand, no action potentials could be detected by electrophysiological investigation of cultured human CC smooth muscle cells (Christ et al, 1993).…”
Section: A Electrophysiologymentioning
confidence: 99%